A new naphthalene derivative with anti-amyloidogenic activity as potential therapeutic agent for Alzheimer's disease. Issue 20 (15th October 2020) - Rivera-Marrero, Suchitil; Bencomo-Martínez, Alberto; Orta Salazar, Erika; Sablón-Carrazana, Marquiza; García-Pupo, Laura; Zoppolo, Florencia; Arredondo, Florencia; Dapueto, Rosina; Daniela Santi, María; Kreimerman, Ingrid; Pardo, Tania; Reyes, Laura; et al.
Graphical abstract: Highlights: New 1-naphthyl derivatives were evaluated as Alzheimer's disease-modifying agents. In silico studies suggest that the compounds 6, 7 and 8 could interfere in the Aβ aggregation pathway. Compounds inhibit Aβ1-42 peptide aggregation in a human microglia cell line model. Compound 8 binds to and decreases Aβ burden in hippocampus of aged 3xTg-AD mice. Compound 8 improves the cognitive and memory performance of aged 3xTg-AD mice. Abstract: The aggregation of β-amyloid peptides is associated to neurodegeneration in Alzheimer's disease (AD) patients. Consequently, the inhibition of both oligomerization and fibrillation of β-amyloid peptides is considered a plausible therapeutic approach for AD. Herein, the synthesis of new naphthalene derivatives and their evaluation as anti-β-amyloidogenic agents are presented. Molecular dynamic simulations predicted the formation of thermodynamically stable complexes between the compounds, the Aβ1-42 peptide and fibrils. In human microglia cells, these compounds inhibited the aggregation of Aβ1-42 peptide. The lead compound 8 showed a high affinity to amyloid plaques in mice brain ex vivo assays and an adequate log Poct/PBS value. Compound 8 also improved the cognitive function and decreased hippocampal β-amyloid burden in the brain of 3xTg-AD female mice. Altogether, our results suggest that 8 could be a novel therapeutic agent for AD.